Analysis of landscape influencing factors of urban waterfront greenways based on the scenic beauty estimation method, taking Tongjian Lake in Hangzhou as an example - Hu, Xiujun; Zou, Xun; Fan, Haiyan (Frontiers in Earth Science, 2023)
In order to assess the unique beauty of Tongjian Lake in Hangzhou, 80 sample photographs were selected for landscape beauty degree assessment using the Scenic Beauty Estimation (SBE) Method. The 14 characteristic influencing factors of landscape photos were extracted according to the SBE value, and the influencing factors with insignificant differences and small bias correlation coefficients were eliminated through multiple linear regression analysis. The results showed that the main factors affecting the expression of the beauty of Tongjian Lake were water ecology, greenway morphology, landscape openness, water area ratio, vegetation color richness, and vignette matching. Combining the above analysis results, the two-dimensional plan, isometric map and three-dimensional space are combined to show the main factors in a visual way, and on this basis, the corresponding optimization strategy is proposed. It provides a reference for future urban waterfront greenway landscape creation.